Title: Some principles in doing autoethnography - Elizabeth (Dr), Ho Kam Kau; (Dr) Honorary, Ki Wing Wah (IJRDO-Journal of Applied Science, 2017)
Autoethnography is a popular research method in the understanding of lived experience in relation with cultural, social and emotional conditions. The paper is going to present a method of doing ‘autoethnography’ with reflective thinking in which 1. the author is a main participant 2. Use layers of reflective thinking 3. Devote to the understanding of culture and emotion in relation of teaching ethnic minority in the learning of Chinese in his or her life situation. At different stages of our life, there are episodes of life experience, which we would like to learn from it and invite others to share. Writing autoethnography is simply a promising way to help us learn from our lived experience. To achieve this purpose, an example of teacher’s autoethnography will be reviewed. It is about the emotional challenge experience of a teacher who begins to teach ethnic minority students the dominant language of Chinese in Hong Kong.